1989
DOI: 10.1161/01.str.20.5.627
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thromboxane synthase inhibition on eicosanoid levels and blood flow in ischemic rat brain.

Abstract: Reperfusion of ischemic brain is associated with production of thromboxane A 2 (TXAJ, a proaggregatory vasoconstrictor. We used an animal model of transient forebrain ischemia to study the effects of 1-benzylimidazole (1-BI), a selective inhibitor of thromboxane synthase, upon cerebral eicosanoid levels and cerebral blood flow. Male Wistar rats were subjected to 30 minutes of four-vessel occlusion. The mean±SEM brain level of TXB 2 , the stable metabolite of TXA 2 , determined after 60 minutes of reperfusion w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…TXA2 from activated platelets causes platelet aggregation and vasoconstriction resulting in the reduction of microcirculatory blood flow in multiple organ systems. Research showed that reducing cerebral TXA2 levels may elevate cerebral blood flow and alleviate ischemic brain damage . It has been reported that the balance between PGI2 and TXA2 is important for the cardiovascular system because PGI2 is a physiologic antagonist of TXA2.…”
Section: Discussionmentioning
confidence: 99%
“…TXA2 from activated platelets causes platelet aggregation and vasoconstriction resulting in the reduction of microcirculatory blood flow in multiple organ systems. Research showed that reducing cerebral TXA2 levels may elevate cerebral blood flow and alleviate ischemic brain damage . It has been reported that the balance between PGI2 and TXA2 is important for the cardiovascular system because PGI2 is a physiologic antagonist of TXA2.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four hours later, animals were rendered ischemic, according to institutional guidelines, by a modification of the four-vessel occlusion technique (Pulsinelli and Brierly, 1979) that had been adapted to include modest hypotension (Globus et al ., 1988 ;Pettigrew et al ., 1989). Rats were anesthetized with a methoxyflurane (Metofane)-filled nose cone while the femoral artery was catheterized .…”
Section: Cannulation and Four-vessel Occlusion Model Of Transient Iscmentioning
confidence: 99%
“…Immediately after energy failure due to ischaemia, liberation of arachidonic acid from damaged cell membranes and subsequent synthesis of TxA2 were observed in ischaemia-reperfusion models [3,11,12]. TxA2 has been implicated in causing reperfusion injury, and selective inhibition of thromboxane synthetase has been shown to alleviate postischaemic tissue damage by reducing the effects of TxA2 on blood flow [13]. TxA2, measured as thromboxane B2 (TxB,), the stable, inactive metabolite of TxA2 could therefore be a useful marker for quantifying reperfusion muscle injury.…”
Section: Introductionmentioning
confidence: 99%